2019
DOI: 10.1016/j.epsl.2019.115748
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between zinc, its isotopes, and the major nutrients in the North-East Pacific

Abstract: Trace metal micronutrients play key roles in photosynthesis by oceanic phytoplankton. Though they are required in much smaller amounts than the major nutrients (P, N, Si), their bioavailable forms are also present in the seawater solution at much lower levels. Relationships between the dissolved chemistry of the nutrient-type trace metals, their stable isotope variations, as well those of the major nutrients, have highlighted the importance of biological and physical processes in the Southern Ocean in controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 58 publications
9
67
0
Order By: Relevance
“…Although Zn is a biologically essential trace metal, dissolved δ 66 Zn mostly exhibits an isotopically light signature in the surface ocean (Conway & John, , ), in contrast to the distribution pattern of Cd isotope composition. However, some studies reported that dissolved δ 66 Zn may exhibit insignificant fractionation or even isotopically heavy signature in oceanic surface water, including the studies observed in the SO, the Tasman Sea, the SEPO, and the subarctic Northeastern Pacific Ocean (Samanta et al, ; Sieber et al, ; Vance et al, ; Wang et al, ; Zhao et al, ). Since culture studies showed that adsorbed Zn is isotopically heavy relative to intracellular Zn, scavenging has first been proposed to be the major process causing the relatively light Zn feature in the surface water (John et al, ; John & Conway, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Zn is a biologically essential trace metal, dissolved δ 66 Zn mostly exhibits an isotopically light signature in the surface ocean (Conway & John, , ), in contrast to the distribution pattern of Cd isotope composition. However, some studies reported that dissolved δ 66 Zn may exhibit insignificant fractionation or even isotopically heavy signature in oceanic surface water, including the studies observed in the SO, the Tasman Sea, the SEPO, and the subarctic Northeastern Pacific Ocean (Samanta et al, ; Sieber et al, ; Vance et al, ; Wang et al, ; Zhao et al, ). Since culture studies showed that adsorbed Zn is isotopically heavy relative to intracellular Zn, scavenging has first been proposed to be the major process causing the relatively light Zn feature in the surface water (John et al, ; John & Conway, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since culture studies showed that adsorbed Zn is isotopically heavy relative to intracellular Zn, scavenging has first been proposed to be the major process causing the relatively light Zn feature in the surface water (John et al, ; John & Conway, ). A recent study using model calculation approach suggested that physical mixing may be one of the processes causing δ 66 Zn variation in the surface water of the Northeastern Pacific Ocean, which may be up to 0.3‰ (Vance et al, ). In addition, Liao and Ho () found that particulate Zn concentrations are significantly correlated with aerosol Zn fluxes in the global ocean, implying the importance of aerosol deposition on Zn cycling in the surface ocean.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations